Samples of creative individuals on the Kazakhstan stage - Abulgazieva, S. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2016)
This article discusses the performed plays on the theme of creative people on the stage of the Kazakh State academic drama theatre named after M.Auezov and the author has analyzed directing solutions and acting skills in the several plays as: “Gypsyserenade” by I. Saparbay, “Poet, angel, love” by A. Tarazi and “Actress” by D. Isabekov